LEGAL PROTECTION OF INTERNALLY DISPLACED PERSONS (IDPs) IN NIGERIA AMIDST CORONAVIRUS (COVID-19) PANDEMIC - Toby, Boma Geoffrey; Ajie, Chukuma; Nwanyanwu, Martina Ebikake (PEOPLE: International Journal of Social Sciences, 2021)
The sudden global attack of the COVID-19 virus came at the heels of 2019 and brought to the fore the need for a binding legal framework for the internally displaced persons scattered over various IDP camps Nationwide. The pandemic, in the face of poor living and congested temporary shelters unsuitable for living, poor sources of clean water, insufficient food provisions, sanitation and unhygienic amenities put the IDPs at greater risk than they were before this time. The known cure, for the time being, is social distancing, handwashing with water and soap and application of alcoholic based solutions regularly. In the light of the above, this paper examines briefly who the homeless are in Nigeria, their challenges and the effect of the recent viral phenomenon; taking into cognizance their right to be protected under various treaties and soft laws discussed below. Recommendations are thus made for a concise binding and enforceable law or a review of existing soft laws which directly lack the force of law to be fully adopted through the necessary reception laws into Nigeria. This is believed will enhance protection of the displaced persons within the Nigerian space, especially during emergencies such as Coronavirus (COVID-19).